HARD- AND SOFTWARE SUPPORT OF DATA AND KNOWLEDGE PROCESSING METHOD WITH CIPHERING ELEMENTS FOR INTERNET - V. A. Vishniakov; D. S. Borodaenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The algorithm modification of dynamic transformation RDF queries in method for mapping relational DB to the RDF model allows to support the ciphering by the way of unity operations for queries coding with inhomogeneous mapping on relational model. Two variants of method of mapping relational DB to the RDF model are proposed. The software realization for medium volume of user queries (until ten thousand) in class terms is proposed. The hardware realization of this method for large volume of user queries (tens and hundreds of thousands) by including to web-server the special processor on PLIS is proposed.